Gender Representation in Eastern Indonesian Songs: A Sara Mills Analysis and Its Implications in Indonesian Language Learning - Yuliana Jetia Moon; I Nyoman Sudiana; I Nengah Suandi; I Putu Mas Dewantara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This article aims to examine how power relations between men and women are portrayed in the lyrics of Eastern Indonesian songs and how the positions of the subject, object, and reader are constructed through Sara Mills' model of Critical Discourse Analysis (CDA). This study also explores the pedagogical potential of utilizing song lyrics in Indonesian language learning based on critical literacy. This study used a qualitative method with documentation techniques applied to four popular song lyrics performed by male and female singers, selected based on regional distribution and number of views. The analysis was conducted by identifying subject–object positions, language strategies, and ideological content within the lyrics. The findings show that women are often represented as social or sexual objects in lyrics sung by men; however, in several songs, women appear as active subjects who express their own will. Gender power relations are revealed through diction choices, sentence structures, and emotional language styles. This study also indicates that Eastern Indonesian song lyrics have the potential to be used as contextual, reflective, and relevant learning texts to develop social awareness and critical thinking skills in Indonesian language classrooms.